EFFECT OF SUB CHRONIC EXPOSURE TO A MIXTURE OF WATER CONTAMINATING HEAVY METALS ON HAEMATOLOGICAL PARAMETERS AND FERTILITY OF FEMALE ALBINO RATS. - TAPASI BHATTACHARJEE; JANHABI SAHA; DIPAYAN CHOUDHURI (International Journal of Pharma and Bio Sciences, 2014)
In an environmental setup both humans and animals are exposed to mixture of heavy metals, especially through drinking water. Little is known about the interactions among various heavy metals during their co-exposure through drinking water and their net combined toxic implications in humans and animals. In current study, we examined the effect of sub chronic exposure via drinking water to a low dose (10 and 100 times mode concentration) mixture of three water contaminating heavy metals arsenic (As), cadmium (Cd) and lead (Pb) on haematological and reproductive parameters of female albino rats. The exposure to mixture for 60 days decreased body weight, weight of ovary and uterus and increased weight of liver and kidney. There was a significant decrease in red blood cell count, white blood cell count, and haemoglobin concentration. The clotting time increased significantly with concomitant decrease in platelet count. Fertility tests by pairing treated females with untreated males showed that mixture treated female were having an irregular oestrus cycle and a significant drop in fertility rate. Pups born to mixture treated animals showed loss in weight, high mortality rate and poor growth rate. The present study revealed that exposure to mixture of water contaminating heavy metals (As,Cd,Pb) caused changes in haematological parameters and affected reproductive performance of female rats at a low sub chronic dose.